The philosophy of customary law - Murphy, James Bernard, 1958- (New York : Oxford University Press, 2014)
This book attempts to bring greater theoretical clarity to the often murky topic of custom by showing that custom must be analysed into two more logically basic concepts: convention and habit. Customs are conventional habits and habitual conventions. Once we have a clearer understanding of custom we can better grasp the many roles that custom plays in a legal system.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on March 17, 2014).
Keywords: Customary law; Customary law -- Philosophy